2019
DOI: 10.3102/0002831218816059
|View full text |Cite
|
Sign up to set email alerts
|

Being “Loud”: Identities-in-Practice in a Figured World of Achievement

Abstract: Discourses of achievement often overlook the interdependence of classroom contexts, students’ identities, and academic performance. This narrative analysis explores how high-achieving students of color construct identities-in-practice in a diverse urban middle school. By documenting explicit moments in which students construct identities-in-practice such as being “loud,” which are positioned as incompatible with “being smart,” I argue that high-achieving lower income students of color are disproportionately re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 72 publications
0
24
0
Order By: Relevance
“…Formal schooling often operates under the assumption that everyone can be a successful student while ignoring the historical, political, cultural, and social influences that create power differentials that make success only applicable to certain students (Carter Andrews, Brown, Castro, & Id‐Deen, 2019; Collins & Bilge, 2016). This power differential can negatively impact the disciplinary identity development of girls of color because White middle class ways of knowing are positively recognized (Caraballo, 2019; Carter Andrews et al, 2019), positioning girls of color and girls from low‐income households to make choices about the ways they perform and the identities they assume when considering ways to be viewed as a good student (Hancock, 2016). As such coding identity development will compete with minoritized youth's other cultural values and the stereotype threats that shape how they act and wish to be seen by others (DiSalvo et al, 2014)—crucial components of identity development.…”
Section: Introductionmentioning
confidence: 99%
“…Formal schooling often operates under the assumption that everyone can be a successful student while ignoring the historical, political, cultural, and social influences that create power differentials that make success only applicable to certain students (Carter Andrews, Brown, Castro, & Id‐Deen, 2019; Collins & Bilge, 2016). This power differential can negatively impact the disciplinary identity development of girls of color because White middle class ways of knowing are positively recognized (Caraballo, 2019; Carter Andrews et al, 2019), positioning girls of color and girls from low‐income households to make choices about the ways they perform and the identities they assume when considering ways to be viewed as a good student (Hancock, 2016). As such coding identity development will compete with minoritized youth's other cultural values and the stereotype threats that shape how they act and wish to be seen by others (DiSalvo et al, 2014)—crucial components of identity development.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a case study examining how middle school girls from minoritized backgrounds engaged in science-related activities, Calabrese Barton et al (2013) found that a particular student's sense of science identity in the classroom was comprised of racial dynamics that did not allow her to capitalize on her love for experiments and project work that developed during her earlier schooling experiences. For many minoritized students of color, a combination of marginalizing sociohistorical narratives and the normative and structured practices of schooling ultimately undermine their sense of creativity and meaningful engagement in science (Caraballo, 2019).…”
Section: Theoretical Framework Figured Worldsmentioning
confidence: 99%
“…Similarly, Boaler and Greeno (2000) found that discourses surrounding math education—math education as memorizing algorithms versus fostering strategic problem solving—shaped classroom activities and rituals, which constructed students’ identities. Later studies also established the ways in which discourses and artifacts, whether physical or conceptual, shape students’ actions and lead to the establishment of social identities (Caraballo 2019; Hatt 2012; Urrieta et al 2011).…”
Section: Theoretical Frameworkmentioning
confidence: 99%